The Precautionary Principle and the Social Standard - Knudsen, Odin K. (World Bank, Washington, DC, 2017)
Scientific progress offers tremendous potential benefits to society but also presents risks. While research focuses on how to manifest the benefits of any new technology, the outside community fears the consequences that technology may inadvertently have on social goods such as the environment, public health and security. To balance the benefits of the progress of science against the risks associated with its application is one of the major public policy challenges of the 21st century. In this paper, the author argues that the precautionary principle is an extension of the scientific method in the popperian tradition and has precedent in hypothesis testing. Under this framework, we then explore an approach that captures the essence of the weaker precautionary principle but also accounts for the 'unacceptable' outcome through the use of a social standard or threshold of harm. Under this methodology, a social standard is established and accounted for in the cost-benefit analysis. The existence of the social standard creates an additional cost or benefit to the assessment of a project. The report illustrates the methodology with a discussion of two cases: the 'mad cow' disease and the regulation on carbon emission.